4. SEKURITISASI KABUT ASAP DI SINGAPURA TAHUN 1997-2014 - Kardina Gultom; Tri Cahyo Utomo; Nadia Farabi (Journal of International Relations Diponegoro, 2016)
Transboundary haze pollution is one of environmental problem in ASEAN countries thathad caused essential impact toward some countries in the region, include Singapore. Thisproblem was caused by illegal conflagration of deforestation by company and citizen inIndonesia. Due to failure of Indonesian government in controlling the forest and landconflagration has encouraged Singapore to do securitization against haze issue. Thisresearch aims to give explanation about haze securitization plot by Singapore governmentin 1997-2014. This research is using Barry Buzan theory about securitization. Thisresearch is using a qualitative method with the explanative type by using interviewsresearch technique and literature reviews. The result of this research is the hazesecuritization in Singapore successfully conducted by Singapore goverment with variety ofsecuritization efforts, such as sending memorandum to Indonesian government, ratificationof ASEAN Agreement on Transboundary Haze Pollution, bilateral cooperation with thepurpose to overcome the haze problem and officially confirmed the Transboundary HazePollution Act.The successful haze securitization was motivated by a big number of citizenrespons toward the problem and the accumulation of total disadvantage suffered bySingapore government. However, haze securitization by Singapore government doesn’tinfluence Indonesia and Singapore bilateral relations. Until now, the relations between theboth countries is maintained well.